The very lonely firefly - Carle, Eric, 1929-2021 (London : Puffin Books, Penguin Random House, 2015)
A light-up surprise for the youngest child from Eric Carle, creator of The Very Hungry Caterpillar. As the sun sets a little firefly is born. The very lonely firefly sets off into the darkening sky, flashing its light as it searches for other fireflies. It sees many lights - including a light bulb, headlights, the reflecting eyes of a dog, cat and owl and finally some fireworks glittering and shimmering - until at last it finds the firefly friends it was looking for. Now the firefly isn't lonely any more. The joyful conclusion of this delightful story is brought vividly to life with tiny flashing lights on the final page to delight young children.
Keywords: anglické rozprávky; publikácie pre deti; leporelá; čítame si spolu 0+; cudzojazyčná literatúra